Mimicking Natural Microenvironments: Design of 3D-Aligned Hybrid Scaffold for Dentin Regeneration - Campodoni, Elisabetta; Dozio, Samuele M.; Panseri, Silvia; Montesi, Monica; Tampieri, Anna; Sandri, Monica (Frontiers in Bioengineering and Biotechnology, 2020)
Tooth loss is a common consequence of a huge number of causes and can decrease the quality of humans’ life. Tooth is a complex organ composed of soft connective tissues and mineralized tissues of which dentin is the most voluminous component whose formation is regulated by a very complex process displaying several similarities with osteogenesis. Calcium phosphates, in particular hydroxyapatite (HA), is the phase present in higher amount into the structure of dentin, characterized by microscopic longitudinal dentinal tubules. To address the challenge of dental tissue regeneration, here we propose a novel biomimetic approach, to design hybrid scaffolds resembling the physico-chemical features of the natural mineralized tissues, suitable to recreate an appropriate microenvironment that stimulates cell colonization and proliferation, therefore effective for improving regenerative approach in dental applications. Biomineralization is the adopted synthesis as a nature inspired process consisting in the nucleation of magnesium-doped-hydroxyapatite (MgHA) nanocrystals on the gelatin (Gel) matrix generating hybrid flakes (Gel/MgHA) featured by a Gel:MgHA weight ratio close to 20:80 and size of 50–70 μm. Chemical and topotactic constrains affect the formation of MgHA mineral phase on the organic template, generating quasi-amorphous MgHA as revealed by XRD analysis and Ca/P ratio lower than 1.67, resembling the chemical and biological features of the natural apatite. The Gel/MgHA was then merged into the polymeric blend made of chitosan (Chit) and Gel to obtain a 3D porous scaffold with polymers: MgHA weight ratio of 40:60 and featured by an aligned porous structure as obtained by controlled freeze-drying process. The overall composite shows a swelling ratio of about 15 times after 6 h in PBS. The chemical stability was assured by means of a dehydrothermal cross-linking treatment (DHT) keeping the degradation lower than 20% after 28 days, while cell adhesion and proliferation were evaluated using a mouse fibroblast cell line.